2001
DOI: 10.1081/ss-100105912
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Copper (Ii) and Chromium (Iii,vi) From Electroplating-Industry Wastewater by Ion Exchange

Abstract: Two laboratory-scale separation processes have been developed for the recovery of copper (II) from acidic and cyanide-containing alkaline wastewater of electroplating industries. Acidic bath wastes were treated with Dowex 50X8, a strongly acidic cation-exchange resin, and the retained copper was eluted with H 2 SO 4 . The cyanide-containing alkaline bath waste was first oxidized with excessive hypochlorite, then neutralized, and recovered by the use of Amberlite IRC-718 chelating resin. Copper was eluted with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…29,34 (12) where K b and n are the Freundlich constants incorporating all parameters affecting the adsorption process. It is reported that 1 ≤ n ≤ 10 represent favourable adsorption conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29,34 (12) where K b and n are the Freundlich constants incorporating all parameters affecting the adsorption process. It is reported that 1 ≤ n ≤ 10 represent favourable adsorption conditions.…”
Section: Resultsmentioning
confidence: 99%
“…2 9,10 Methods for the removal of Cr (VI) involve chemical precipitation, electrolysis, biochemical process, and adsorption. 11,12 Phosphorus is one of the major nutrients for plant growth and it comes from agricultural fertilisers, soaps, and detergents with formulations containing sodium tripolyphosphates, atmospheric nitrogen, erosion of soils containing nutrients, and discharge from sewage treatment plants. 7,13 Though it is an essential macronutrient responsible for healthy plant growth, concentration in an excess of the described limit can result in the eutrophication of lakes, rivers, and seas.…”
Section: Introductionmentioning
confidence: 99%
“…the hydrolysis products held by the resin may be resistant to dilute acids [24], and since stronger acid eluents would not be selective for Cr(III) among other metals, Cr(III) was preferentially eluted with an alkaline solution (ammonia buffer) containing H 2 O 2 so that the oxidation product (CrO 4 2-) would be rejected by the XAD-POx chelating cation exchanger column. Thus selectivity was achieved for Cr(III).…”
Section: Resultsmentioning
confidence: 99%
“…Next, a sample was treated by alkaline chlorination for cyanide destruction. The method involved overnight treatment with 2.0 mol L À1 NaOCl for total oxidation of cyanide to inorganic carbon (Yalçin et al, 2000). The precipitate was dissolved in 1.0 mol L À1 H 2 SO 4 to yield a final solution with metal concentrations of 200 mg L À1 , 14.4 mg L À1 , and 65.5 mg L À1 of Cu 2þ , Ni 2þ and Zn 2þ ions, respectively.…”
Section: Breakthrough Curvesmentioning
confidence: 99%